Trends in Astrophysics and Cosmology Research in the period 2016 – 2024: A Systematic Literature - Theodora Lyas Pita Simamora; Nafila Zahira; Yelsa Maria Sitanggang; Jubaidah; Rugaya (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze trends in astrophysics and cosmology research from 2016 to 2024 using a Systematic Literature Review (SLR) of 31 academic papers. The study identifies dominant topics, emerging methodologies, and existing challenges in the field. The increasing role of computational techniques and the need for improved theoretical models in cosmology highlight the significance of this research. The study employs a systematic review approach, selecting 31 peer-reviewed articles from arXiv and Physical Review D. The articles are classified based on research focus and methodology, including theoretical modeling, observational studies, computational simulations, and experimental research. Thematic and trend analysis was conducted to map developments in the field. The review indicates that black hole studies (80%) and gravitational waves (50%) are the most prominent topics. Major advances include the first image of a black hole captured by Event Horizon Telescope (EHT) and improved gravitational wave detection by LIGO. Computational astrophysics, particularly machine learning, has enhanced data analysis and theoretical modeling. However, studies on dark matter (0%) and dark energy (1%) remain limited, and unresolved issues like the Hubble Tension suggest the need for alternative cosmological models. This study is limited by the selection of 31 papers, which may not fully capture all research advancements. Additionally, the rapid evolution of astrophysical research necessitates continuous updates with larger datasets and interdisciplinary methodologies. Future research should focus on refining cosmological models, integrating multimessenger observations, and advancing quantum gravity studies